Fruit and Vegetable Intake: Benefits and Progress of Nutrition Education Interventions- Narrative Review Article - Dhandevi PEM; Rajesh JEEWON (Tehran University of Medical Sciences, 2015)
Background: Sufficient intake of fruits and vegetables has been associated with a reduced risk of chronic diseases and body weight management but the exact mechanism is unknown. The World Health Organisation and Food and Agriculture of the United Nation reports recommend adults to consume at least five servings of fruits and vegetables per day excluding starchy vegetables. This review focuses on the importance of fruits and vegetables as well as the benefits and progress of nutrition education in improving intake. Methods: For this narrative review, more than 100 relevant scientific articles were considered from various databases (e.g Science Direct, Pub Med and Google Scholar) using the keywords Fruit and vegetable, Nutrition education, Body weight, Obesity, Benefits and challenges. Results: Existing data suggests that despite the protective effects of fruits and vegetables, their intakes are still inadequate in many countries, especially developing ones. Consequently enhancing strategies to promote fruit and vegetable intake are essential for health promotion among population. A number of reviews confirm that a well planned and behaviour focused nutrition education intervention can significantly improve behaviour and health indicators. Conclusion: Despite challenges in nutrition education intervention programs, they are considered as a good investment in terms of cost benefit ratio. Rapid improvement in trends of nutrition education can be seen in many countries and majority of interventions has been successful in increasing fruits and vegetables intake. It is recommended that health professionals use multiple interventions to deliver information in several smaller doses over time to ensure improved outcomes.   Keywords: Fruit and vegetable, Nutrition education intervention, Body weight, Obesity, Benefit and challenges.